2015
DOI: 10.1093/humrep/dev030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ulipristal acetate on human embryo attachment and endometrial cell gene expression in an in vitro co-culture system

Abstract: Swedish Research Council (K2010-54X-14212-09-3) and support provided through the regional agreement on medical training and clinical research (ALF) between Stockholm County Council and Karolinska University Hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 80 publications
(95 reference statements)
2
26
1
2
Order By: Relevance
“…It does not appear to impair sperm function [47]. Some studies have shown that UPA may alter certain endometrial parameters, although in-vitro studies show no difference in the ability of embryos to implant when exposed or not exposed to UPA [48]. The best available evidence suggests that the primary mechanism of UPA in doses used for EC is interference with ovulation [16, 49].…”
Section: Ulipristal Acetatementioning
confidence: 99%
“…It does not appear to impair sperm function [47]. Some studies have shown that UPA may alter certain endometrial parameters, although in-vitro studies show no difference in the ability of embryos to implant when exposed or not exposed to UPA [48]. The best available evidence suggests that the primary mechanism of UPA in doses used for EC is interference with ovulation [16, 49].…”
Section: Ulipristal Acetatementioning
confidence: 99%
“…This means that UPA has a wider window of action than LNG and remains effective in the immediate preovulatory phase when the risk of conception is greatest, hence explaining its higher efficacy compared with LNG in clinical trials . Postovulatory administration of UPA at the EC dose may induce some immunohistochemical and molecular changes in the endometrium, but other in vitro studies have shown that UPA at concentrations relevant for EC do not interfere with embryo attachment to the endometrium . UPA at pharmacological concentrations can suppress ciliary beating and muscular contractility in fallopian tube, as well as modulate sperm function by inhibiting sperm hyperactivation, progesterone‐induced acrosome reaction and calcium influx .…”
Section: Mechanisms Of Action Of Ecmentioning
confidence: 99%
“…Indirect evidence from in vitro studies also showed that LNG or UPA at EC doses had no effect on human blastocyst viability in spite of sufficient time being allowed for the embryo to undergo any degenerative changes that LNG or UPA could possibly cause within the culture system.…”
Section: Safety Of Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in vitro models using epithelial cells provide a useful means with which to investigate potential interactions that might occur in vivo, and allow workers to systematically evaluate the complex network of biological pathways involved in implantation (Teklenburg and Macklon, 2009;Weimar et al, 2013;Berger et al, 2015).…”
Section: In Vitro Modelsmentioning
confidence: 99%